Pediatric laparoscopic cholecystectomy with 2.3 mm Percutaneous Surgical System (MiniLap®): A new frontier for pediatric mini laparoscopy? - Filomena Valentina Paradiso; Lorenzo Nanni (Elsevier, 2016)
Mini-laparoscopy represents an evolving and attractive field both in general and in pediatric surgery, with a pressing and increasing technical demand. Although the advantages of the mini-laparoscopic approach (reduced morbidity, less incisional pain and discomfort, better cosmetic results) are well recognized, its technical difficulties due to the lack of suitable and comfortable instruments brought to a limited use. Moreover, in the pediatric population, the need of ergonomic mini-invasive but efficient devices is the key of a widespread use of mini-laparoscopic surgery performed with an effective and safe technique. We aim to highlight the first case of pediatric laparoscopic cholecystectomy performed with 2.3 mm percutaneous instruments (MiniLap® Percutaneous Surgical System, Teleflex Incorporated, USA) that represents a significant advance in minimally invasive surgery.